2020
DOI: 10.3389/fgene.2020.577053
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analyses of β-Thalassemia −28(A>G) Mutation Using Isogenic Cell Models Generated by CRISPR/Cas9 and Asymmetric Single-Stranded Oligodeoxynucleotides (assODNs)

Abstract: Analyses of β-Thalassemia −28(A>G) Mutation Using Isogenic Cell Models Generated by CRISPR/Cas9 and Asymmetric Single-Stranded Oligodeoxynucleotides (assODNs).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…On hemoglobin electrophoresis, he had an elevated HbA2 fraction (5.4%) (normal range 1.7-3.2), normal HbF (1.0%) (normal range 0-1.0), and HbH inclusion bodies were not detected. Thalassemia genotyping showed that he is heterozygous for HBB (NM_000518.5):c.-78A>G, a known prevalent pathogenic variant in the ethnic Chinese population (Li et al, 2020).…”
Section: Case Reportmentioning
confidence: 99%
“…On hemoglobin electrophoresis, he had an elevated HbA2 fraction (5.4%) (normal range 1.7-3.2), normal HbF (1.0%) (normal range 0-1.0), and HbH inclusion bodies were not detected. Thalassemia genotyping showed that he is heterozygous for HBB (NM_000518.5):c.-78A>G, a known prevalent pathogenic variant in the ethnic Chinese population (Li et al, 2020).…”
Section: Case Reportmentioning
confidence: 99%
“…Interestingly, the abnormalities due to the −28(A>G) mutation were corrected by CRISPR/Cas9 and asymmetric assODNs in K562 −28( A > G ) . This study is the first to report on the whole-transcriptome analysis based on isogenic cell lines, thus it provides a platform to conduct future investigation of the mechanism of −28(A>G) β-thalassemia ( 50 ).…”
Section: Genome Manipulation Strategiesmentioning
confidence: 99%
“…In vivo editing of the promoter in β-YAC/CD46tg mice resulted in a 20% conversion rate in HSPCs and >40% γ-globin expression in peripheral RBCs [ 73 ]. The HBB -28A>G mutation is one of the most frequently detected mutations in β-thalassemia patients in China and East Asia preventing the transcription of the HBB gene [ 74 ]. Two base editor variants, the eA3A-BE and eA3A(N57Q)-BE3, were employed in erythroid precursor cells derived from a compound heterozygous thalassemia patient (4bp-deletion in exon 1 of one HBB allele and HBB -28 A>G mutation in the other), and they effectively generated the C>G substitution in HBB-28.…”
Section: Double-strand Break-free Gene Editingmentioning
confidence: 99%